Partial Bone Necrosis Following Sagittal Split Ramus Osteotomy: Report of a Complicated Orthognathic Jaw Surgery. (23rd March 2022) - Alalawy, Haider; Kadhum, Ammar S.; Abdulnabi, Hussein A.
Study Design: Case Report. Objective: To present a case of a previous complicated mandibular orthognathic surgery that aimed to setback the mandible in a female cleft lip and palate (CLP) patient, which led to bone necrosis on one side with subsequent severe mandibular deviation and facial asymmetry. We additionally reviewed the previous reports of similar complications, the pathophysiology and the factors that could lead to this dreadful result. Method: A 27-year-old female patient presented with a severe dentofacial deformity secondary to a complicated bilateral sagittal split ramus osteotomy performed five years earlier, which resulted in aseptic bone necrosis on the right side. The patient had marked mandibular deviation, chin and midface retrusion and a pronounced occlusal discrepancy. Imaging demonstrated a bony defect at the right mandibular angle with a superiorly displaced proximal segment. Deviation of the mandible was corrected first by performing vertical ramus subsigmoid osteotomy (RSO) on the left side. The right bone defect was then reconstructed with a reconstruction plate and bone grafting. Maxillary and chin advancement was performed at a second stage. Results: On follow-up, the patient shows a significant improvement in facial esthetics and mandibular symmetry and is currently under orthodontic management to enhance the occlusal relationship. Conclusion: Bone necrosis is a rare but dreaded problem in orthognathic surgery. Minimizing the musculo-periosteal dissection and competent execution of the bone osteotomy is substantially effective in reducing the risk of bone ischemia and necrosis.